Re-examining the Role of Coping Strategies in the Associations Between Infertility-Related Stress Dimensions and State-Anxiety: Implications for Clinical Interventions With Infertile Couples - Zurlo, Maria Clelia; Cattaneo Della Volta, Maria Francesca; Vallone, Federica (Frontiers in Psychology, 2020)
Research has shown a direct relationship between infertility-related stress and anxiety in infertile patients. The present study goes into this relationship in depth, testing the moderating role of coping strategies (Seeking Social Support, Avoidant, Positive Attitude, Problem-Solving, Turning to Religion) in the associations between specific infertility-related stress dimensions (Social Concern, Need for Parenthood, Rejection of Childfree Lifestyle, Couple’s Relationship Concern) and State-Anxiety among male and female partners of infertile couples. Gender differences were also explored. Both members of 254 infertile couples completed a questionnaire consisting of Socio-demographics, Fertility Problem Inventory-Short Form, Coping Orientation to Problem Experienced-NIV, and State-Trait Anxiety Inventory-Y. The results revealed that Social Concern and Couple’s Relationship Concern, in both partners, and Need for Parenthood, in female partners, had positive correlations with State-Anxiety. Seeking Social Support and Avoidant coping were related to increasing levels of State-Anxiety in both partners, whereas Positive Attitude coping strategies were related to lower levels of State-Anxiety in female partners. Problem-Solving and Avoidant coping played moderating roles between specific infertility-related stress dimensions and State-Anxiety in unexpected directions. Problem-Solving exacerbated the negative effects of Social Concern, whereas Avoidant coping buffered the negative effects of several infertility-related stress dimensions in both partners. Interventions to improve stress management and psychological health in infertile couples should consider that the adequacy of coping strategies is inherently situation-specific. It therefore follows that patient-centered clinical interventions should consider the potential inadequacy of promoting Problem-Solving strategies, and that even Avoidance can be an efficient strategy for dealing with specific infertility-related stress dimensions.